1997
DOI: 10.1016/s0014-5793(97)01216-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucocorticoids on the synthesis of antimicrobial peptides in amphibian skin

Abstract: Gene-encoded peptide antibiotics are widespread in insects, plants and vertebrates and confer protection against bacterial and fungal infections. NF-κΒ is an important transcription factor for many immunity-related mammalian proteins and also for insect immune genes. The activity of NF-KB is regulated by the interaction with an inhibitor, ΙκΒ. It was recently demonstrated that glucocorticoids induce the synthesis of IKB in human cell lines. So far, all genes for peptide antibiotics have promoter motifs with NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
1
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 27 publications
(35 reference statements)
4
67
1
3
Order By: Relevance
“…Our in vivo observations are consistent with a study on human fetal lung explants, which demonstrated that hBD-2 mRNA expression was reduced by dexamethasone treatment, while expression of hBD-1 mRNA was increased (45). Similarly, frogs treated with corticosteroids had reduced expression of antimicrobial peptides and failed to reduce the number of bacteria in an experimental oral infection compared to untreated frogs (43,44). The reduction of antimicrobial peptide expression by glucocorticoids seems counterintuitive, as circumstances that elevate endogenous glucocorticoids, such as stress or infection, would likely benefit from the induction of epithelial antimicrobial activity.…”
Section: Discussionsupporting
confidence: 90%
“…Our in vivo observations are consistent with a study on human fetal lung explants, which demonstrated that hBD-2 mRNA expression was reduced by dexamethasone treatment, while expression of hBD-1 mRNA was increased (45). Similarly, frogs treated with corticosteroids had reduced expression of antimicrobial peptides and failed to reduce the number of bacteria in an experimental oral infection compared to untreated frogs (43,44). The reduction of antimicrobial peptide expression by glucocorticoids seems counterintuitive, as circumstances that elevate endogenous glucocorticoids, such as stress or infection, would likely benefit from the induction of epithelial antimicrobial activity.…”
Section: Discussionsupporting
confidence: 90%
“…Activation of such transcription factors and binding to their consensus sequences have also been observed in fish (25,31,32). This suggests that the flounder may regulate pleurocidin gene expression in response to infection and inflammation, in a manner similar to that seen for antimicrobial peptide genes from amphibians (27,38), insects (11), and mammals (9).…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, we showed that treatment of frogs with glucocorticoids results in the up-regulation of IkBa and almost complete inhibition of the de novo synthesis of antimicrobial peptides in skin secretions [13,14].…”
mentioning
confidence: 91%